2022
DOI: 10.1146/annurev-publhealth-051920-123206
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Rise of Suicide Mortality in the United States

Abstract: Suicide is a major public health concern in the United States. Between 2000 and 2018, US suicide rates increased by 35%, contributing to the stagnation and subsequent decrease in US life expectancy. During 2019, suicide declined modestly, mostly owing to slight reductions in suicides among Whites. Suicide rates, however, continued to increase or remained stable among all other racial/ethnic groups, and little is known about recent suicide trends among other vulnerable groups. This article ( a) summarizes US su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 115 publications
1
28
0
Order By: Relevance
“… 8 – 10 Yet, the number of completed suicides has been rising for most of the last two decades. 1 Population data suggest that increased access to firearms and lethal means, worsening structural marginalization, 11 and the COVID-19 pandemic have exacerbated the risk for suicide. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“… 8 – 10 Yet, the number of completed suicides has been rising for most of the last two decades. 1 Population data suggest that increased access to firearms and lethal means, worsening structural marginalization, 11 and the COVID-19 pandemic have exacerbated the risk for suicide. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…25 Nevertheless, research suggests that there are multiple reasons for the choice of method, especially accessibility, familiarity, and social acceptability, and choice of method is often influenced by cultural, religious, and social factors. 13,26,27 Future research might be warranted to understand the changes in mechanisms over time, including changes in access.…”
Section: Article In Pressmentioning
confidence: 99%
“…This study adds to the existing literature by identifying health disparities related to the intesection of multiple social and demographic factors. It is well documented that suicide rates differ by race/ethnicity 13,14 and age group, 4 illustrating the important roles these factors play in risk and protection for suicide. Health disparities are differences in health status between people related to social or demographic factors such as race/ethnicity, sex or geographic region.…”
Section: Introductionmentioning
confidence: 99%
“…In the US, stress-induced conditions like major depressive disorder, bipolar disorder, and generalized anxiety disorder were significant contributors to the increase in mental illness before the pandemic, and a recent review suggested that the point-prevalence of these disorders increased by 30% to 50% during the pandemic [ 6 ]. This is of significant concern since suicide rates in the US have already increased by 35% from 2000 to 2018 [ 7 ]. The wide overlap in symptoms between various disorders like major depression, bipolar I and II disorder, and generalized anxiety disorder are implicitly confounding.…”
Section: Introductionmentioning
confidence: 99%